Microstructure of superconducting Hg0.5Cr0.5Sr2CuO4+delta thin films on SrTiO3 - Kong, G; Jones, I; Abell, J; Jones, M; Edwards, P (2002)
Transmission electron microscopy has been used to characterise the microstructures of Sr2Cr0.5CuO2 precursor thin films and annealed Hg0.5Cr0.5Sr2CuO4+δ thin films on (0 0 1) SrTiO3 substrates. Precursor films consist essentially of amorphous Sr2CuO3 phase with SrCrxCuO2 grains embedded, while Hg0.5Cr0.5Sr2CuO4+δ films are epitaxial with the orientation relationship (0 0 1)Hg∥(0 0 1)STO, [1 0 0]Hg∥[1 0 0]STO. Hg and Cr diffuse through the whole film thickness. Some a-axis grains are present in the Hg0.5Cr0.5Sr2CuO4+δ films with much lower Hg and Cr contents. © 2002 Elsevier Science B.V. All rights reserved.